2020
DOI: 10.7861/clinmed.2020-0369
|View full text |Cite
|
Sign up to set email alerts
|

React, reset and restore: Adaptation of a large inflammatory bowel disease service during COVID-19 pandemic

Abstract: Introduction Healthcare organisations have had to make adaptations to reduce the impact of the Coronavirus 2019 (COVID-19) pandemic. This has necessitated urgent reconfiguration within inflammatory bowel disease (IBD) services to ensure safety of patients and staff and seamless continuity of care provision. Aim To describe the adaptations made by a large inflammatory bowel disease service, caring for over 3,500 IBD patients, in response to the COVID-19 pandemic. Methods A diary record of responses to the pande… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…In IBD, significantly improved medication adherence and reductions in outpatient visits and hospitalisations were reported with telemedicine versus standard care prior to the pandemic [ 110 , 111 ]. During the pandemic, a UK survey reported that telephone consultations replaced 86% of face-to-face clinics for patients with IBD [ 112 ]; in one unit, 92% of patients who had a consultation via telephone rather than in person were satisfied with their experience [ 102 ]. Gastroenterologists have also reported patient preferences for virtual management approaches during the pandemic and have described the value of SC biologics, including CT-P13 SC, in delivering home care-based management [ 71 ].…”
Section: Clinical Implications Of Sc Infliximab In the Covid-19 Pandemic Era And Beyondmentioning
confidence: 99%
See 1 more Smart Citation
“…In IBD, significantly improved medication adherence and reductions in outpatient visits and hospitalisations were reported with telemedicine versus standard care prior to the pandemic [ 110 , 111 ]. During the pandemic, a UK survey reported that telephone consultations replaced 86% of face-to-face clinics for patients with IBD [ 112 ]; in one unit, 92% of patients who had a consultation via telephone rather than in person were satisfied with their experience [ 102 ]. Gastroenterologists have also reported patient preferences for virtual management approaches during the pandemic and have described the value of SC biologics, including CT-P13 SC, in delivering home care-based management [ 71 ].…”
Section: Clinical Implications Of Sc Infliximab In the Covid-19 Pandemic Era And Beyondmentioning
confidence: 99%
“…Telemedicine and contactless healthcare are expected to continue to grow post-pandemic as key concepts of future healthcare systems (Table 1 ) [ 2 , 69 , 99 102 ]. Indeed, acceptance of digital tools increased during the pandemic [ 105 ].…”
Section: Clinical Implications Of Sc Infliximab In the Covid-19 Pandemic Era And Beyondmentioning
confidence: 99%
“…Several recent publications have described the restrictions imposed by COVID-19 alongside prioritization and newer models of care in A&I and other medical and surgical specialties. [5][6][7][8][9] Specifically, the British Society for Allergy and Clinical Immunology (BSACI), the European Academy of Allergy and Clinical Immunology, and the American Academy of Allergy, Asthma & Immunology issued expert/consensus guidance regarding safe and strategic delivery of specialist A&I services during the pandemic. [10][11][12] We sought to assess the impact of COVID-19 pandemic on A&I services within secondary health care NHS facilities in the United Kingdom.…”
Section: Introductionmentioning
confidence: 99%
“…The urgent requirement for non-invasive indices in IBD is additionally augmented by the recent global growth in IBD incidence rates [24]. Furthermore, the current COVID-19 pandemic highlighted the significance of non-invasive point-of-care tests, that may be integrated with telemedicine in IBD patient care [25][26][27].…”
Section: Introductionmentioning
confidence: 99%